2017
DOI: 10.1111/odi.12661
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation pattern of apoptosis‐related genes in ameloblastoma

Abstract: On the basis of our results, the transcription of the apoptosis-related gene BCL2L11 is possibly regulated by promoter DNA methylation in ameloblastoma. The biological significance of this finding in ameloblastoma pathobiology remains to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Moreover, miR-10b overexpression and HOXA1 knockdown resulted in aberrant DNMT expression and an increased embryo apoptosis ratio. Previous findings in human cancer cells have shown that cell apoptosis and cell proliferation are related to DNA methylation, and DNA methylation can help inactivate apoptotic pathways at several points (Cho et al, 2011; Ye et al, 2016; Costa et al, 2017; Loginov et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-10b overexpression and HOXA1 knockdown resulted in aberrant DNMT expression and an increased embryo apoptosis ratio. Previous findings in human cancer cells have shown that cell apoptosis and cell proliferation are related to DNA methylation, and DNA methylation can help inactivate apoptotic pathways at several points (Cho et al, 2011; Ye et al, 2016; Costa et al, 2017; Loginov et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were incubated at 37°C for 6 h. Then quantitative PCR (qPCR) was performed using the RT2 SYBR Green ROX qPCR Master Mix (Qiagen, Hilden, Germany) according to the manufacturer’s recommendations in a Step One Plus Real-Time PCR System (Applied Biosystems, Foster City, CA, USA). Threshold cycle (Ct) values were utilized to calculate the percentages of methylated (M) and unmethylated (UM) DNA, using a quantization algorithm provided by the manufacturer to normalize the amount of DNA in each digestion against the total amount of input DNA in the mock digestion, using the Excel macro-spreadsheet supplied by the manufacturer (Qiagen, Hilden, Germany) [25-27].…”
Section: Methodsmentioning
confidence: 99%
“…Another possible mechanism contributing to tumorigenesis of ameloblastoma seems to be DNA hypomethylation of transcription related genes. A recent study showed a lower methylation rate significantly of the promoter region of BCL‐2 in ameloblastomas in comparison with regular dental follicles (Costa et al., ).…”
Section: Recent Molecular Pathogenic Findings and Implications For Tamentioning
confidence: 99%